77 Do nudge-type interventions change clinician treatment, screening, and testing behaviours?: a systematic review. (20th August 2018) - O'Keeffe, Mary; Traeger, Adrian; Hoffmann, Tammy; Bonner, Carissa; Soon, Jason; Maher, Chris
Abstract : Objectives: To review all randomised controlled trials that have assessed the effect of nudge-type interventions on clinician treatment, screening, and testing behaviours across all health conditions. Method: A systematic review of randomised controlled trials. Two reviewers are conducting the electronic searches of six databases independently. We are defining a nudge as any simple, brief, low-cost, individual level, easy to avoid intervention intentionally designed to alter the presentation or framing of choices or information within the clinician's immediate environment (the clinical setting) to target and change a specific clinician behaviour in a predictable way, while preserving the clinician's freedom of choice, and not forbidding any clinician options/behaviours. Studies comparing nudge type interventions to usual care, non-nudge interventions or sham nudges will be included. Studies measuring changes in treatment delivery, testing, and screening utilisation will be included. These will include any procedure, test or treatment. The GRADE approach as recommended in the Cochrane Handbook for Systematic Reviews of Interventions will be used to assess to overall quality of evidence. Results: The review is still in progress, and so the results are unavailable at this time. Conclusions: Finding effective ways to change clinician behaviour to ensure the provision of high-value care, and the removal of low-value or harmful care, is a priority across healthcare systems. The concept of nudging has gained traction in policy circles and as a way to improve health care delivery, but empirical evidence to support this idea is limited, especially its application to changing clinician behaviour. We do not know if there is robust evidence to show that nudging is better at changing clinician behaviours over standard usual care practices. Furthermore, depending on the targeted health condition and the specific nudge being used, it is unclear if the nudge is aiming to change clinician behaviour, to promote low value or high value healthcare (e.g. nudges to increase or decrease screening). This will be the first ever systematic review to provide results on the effect of nudging on clinician behaviours.